Authoritarian Parenting Practices on Korean Drama: Reception Analysis on SKY Castle - Setianoto, Fiona Angeline; Primadini, Intan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pembangunan Nasional Veteran Jakarta, 2024)
The Korean drama